STRUKTUR DAN KAIDAH KEBAHASAAN PADA TEKS PROSEDUR SISWA SMP NEGERI 8 PONTIANAK - Hanna, Hanna; Wartiningsih, Agus; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to analyze the structure and the language rules of procedure texts by students of SMP Negeri 8 Pontianak in Indonesian language learning. The method used in this research is descriptive with qualitative research form. The data collection technique used was documentary study. The data source of this research is the procedure text of the work of class VII D students totaling 35 at SMP Negeri 8 Pontianak in the 2023/2024 school year. The data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. The results of the research analysis from the structure aspect as many as 28 students made the essay got an assessment score of 50 with very good assessment criteria, 7 students got an assessment score of 40 with good assessment criteria, from the aspect of language rules as many as 8 students made the essay got an assessment score of 60 with very good assessment criteria, 15 students got an assessment score of 50 with very good assessment criteria, 9 students got an assessment score of 40 with good assessment criteria, 2 students got an assessment score of 30 with sufficient assessment criteria, 1 student got an assessment score of 10 with very poor assessment criteria.